Study on the growth performance of rubber seedlings using bio-organic fertilizer / Mohamad Syazwan M. Rosley - M. Rosley, Mohamad Syazwan (Faculty of Plantation and Agrotechnology, 2015)
The precise use of fertilizers is very important in a rubber nursery establishment to ensure quality production of planting materials and optimizations of the fertilizing cost. This study was conducted for two month periods to see the growth performance of rubber seedlings using different type of fertilizers and different percentage rate of combination fertilizer. The objective of this study is to observe whether bio-organic fertilizer can replace NPK yellow (control) fertilizer and to identify the best combination of bio-organic fertilizer with NPK Yellow fertilizer. Alfa Life fertilizer was used to represent bio-organic fertilizer while NPK Yellow fertilizer as the control fertilizer that been recommended by Malaysia Rubber Board (MRB). The study was carried out at greenhouse in UiTM Jasin, Melaka. The experiment was laid out in a Complete Randomized Design (CRD) with five treatments and four replications.T0 (100% NPK Yellow) and T1 (100% AL) was compared to see whether bio-organic can replace NPK yellow while T2 (75% NPK Yellow + 25% AL), T3 (50% NPK Yellow + 50% AL) and T4 (25 % NPK Yellow + 75% AL) have been identified as the best combination of treatments. Data on growth such as seedling height, stem girth, leaves dry weight, stem dry weight and root dry weight were collected. The data was tested with Analysis of Variances (ANOVA) and grouping information using Tukey method by using Minitab 16.1. Result showed that there were no significant differences among the five treatments and all treatments have been shared the same group "A" for five parameters. TO have better mean in seedling height, stem girth, leaves dry weight and root dry weight than T1. So, this result showed Alfa Life (bioorganic) fertilizer is not able to compete with NPK Yellow (control) due to no significant difference between both of them. The best combinations of the three treatments were T4 which consist of 25% of NPK Yellow and 75% of Alfa Life fertilizer. The highest mean for all parameters were T4 which is the best treatment among the five treatments. The fertilizer combinations of T4 have the better result than the control fertilizer. Thus, fertilizer combination of T4 is recommended to replace TO (control fertilizer).